Human paleontology and prehistory : contributions in honor of Yoel Rak - Marom, Assaf; Hovers, Erella; Rak, Yoel (Vertebrate paleobiology and paleoanthropology., 2017)
The aim of the book is to present original and though-provoking essays in human paleontology and prehistory, which are at the forefront of human evolutionary research, in honor of Professor Yoel Rak (a leading scholar in paleoanthropology). The volume presents a collection of original papers contributed by many of Yoel's friends and colleagues from all over the globe. Contributions from experts around the globe fall roughly into three broad categories: Reflections on some of the broad theoretical questions of evolution, and especially about human evolution; the early hominins, with special emphasis on Australopithecus afarensis and Paranthropus; and the Neanderthals, that contentious group of our closest extinct relatives. Within and across these categories, nearly every paper addresses combinations of methodological, analytical and theoretical questions that are pertinent to the whole human evolutionary time span. This book will appeal most to scholars and advanced students in paleoanthropology, human paleontology and prehistoric archaeology.